Bistro De Sinaran Cafe', No. 1, Jalan Laksamana, Bandar Hilir, Melaka [microfilm] - Ahmad Zukhairi Sulaiman; Mohd. Asma Husni Mat Nawi; Mohd. Khuzaimi Yusoff; Nur Azyyati Mat Jelan; Salina Long; Zurika Amnah @ Salmi Mohtar (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Measured Drawing (Jabatan Senibina)) - Universiti Teknologi Malaysia, 2003